Newborn screening for sickle cell disease: an innovative pilot program to improve child survival in Dar es Salaam, Tanzania. Issue 6 (30th May 2019) - Nkya, Siana; Mtei, Lillian; Soka, Deogratias; Mdai, Vera; Mwakale, Promise B; Mrosso, Paul; Mchoropa, Issa; Rwezaula, Stella; Azayo, Mary; Ulenga, Nzovu; Ngido, Melkiory; Cox, Sharon E; et al.
Abstract: Background: Sickle cell disease (SCD) is a recognized cause of childhood mortality. Tanzania has the fifth highest incidence of SCD (with an estimated 11 000 SCD annual births) worldwide. Although newborn screening (NBS) for SCD and comprehensive healthcare have been shown to reduce under-5 mortality by up to 94% in high-income countries such as the USA, no country in Africa has maintained NBS for SCD as a national health program. The aims of this program were to establish and evaluate NBS-SCD as a health intervention in Tanzania and to determine the birth prevalence of SCD. Methods: Muhimbili University of Health and Allied Sciences conducted NBS for SCD from January 2015 to November 2016. Dried blood spot samples were collected and tested for SCD using isoelectric focusing. Results: Screening was conducted on 3981 newborns. Thirty-one (0.8%) babies had SCD, 505 (12.6%) had sickle cell trait and 26 (0.7%) had other hemoglobinopathies. Twenty-eight (90.3%) of the 31 newborns with SCD were enrolled for comprehensive healthcare. Conclusions: This is the first report on NBS as a health program for SCD in Tanzania. The SCD birth prevalence of 8 per 1000 births is of public health significance. It is therefore important to conduct NBS for SCD with enrollment into a comprehensive care program.